2002
DOI: 10.1089/109493102321018150
|View full text |Cite
|
Sign up to set email alerts
|

Users Divided? Exploring the Gender Gap in Internet Use

Abstract: Many believe that males and females use and regard computer technology differently. Males are generally assumed to be more comfortable with, more adaptable to, and less anxious with computer technology. The same biases are now being applied specifically to Internet technology. Based on research showing that men prefer to use the Internet for information gathering and entertainment, while women prefer to use the Internet for interpersonal communication, this study examined the effects of Internet use when both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
73
2
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(97 citation statements)
references
References 18 publications
13
73
2
3
Order By: Relevance
“…The results reflected that the gender gap in Internet usage among the respondents was marginal and almost nonexistent and females in this study spent as much time on the Internet as their male counterparts. The results of this study were consistent with the earlier findings of Odell et al [18] and Shaw and Gant [17] . They reported that the gender gap in the use of the Internet has been narrowing in recent years.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results reflected that the gender gap in Internet usage among the respondents was marginal and almost nonexistent and females in this study spent as much time on the Internet as their male counterparts. The results of this study were consistent with the earlier findings of Odell et al [18] and Shaw and Gant [17] . They reported that the gender gap in the use of the Internet has been narrowing in recent years.…”
Section: Discussionsupporting
confidence: 93%
“…The Internet is a potential source of knowledge, information as well as a platform for social interaction. As such, Internet usage is usually motive driven --mainly for the three aspects of communication, information gathering and entertainment [17] .…”
Section: Instrumentation Validation and Pilot Testmentioning
confidence: 99%
See 1 more Smart Citation
“…18 However, there were studies that found no gender gap in Internet activities. 19 To our knowledge, however, no research has explored gender differences in the relationship between VW and RW activities.…”
Section: Gender Differences In Vw and Rw Activitiesmentioning
confidence: 99%
“…De hecho, los datos del presente trabajo cuestionan otros estudios que afirman que la brecha de género en relación con Internet y otros medios está disminuyendo o no se percibe entre los más jóvenes (Shaw & Gant, 2002) o, como señala el Mobile World Capital (2016), no influye en la brecha digital y, por lo tanto, no necesitaría un trato especial. El artículo pone en el punto de mira las diferencias de género que perviven en nuestros jóvenes en sus consumos mediáticos y nos alerta sobre la necesidad de tomar medidas de actuación.…”
Section: Conclusionesunclassified